(untitled) (Journal of Civil Engineering Researchers, 2023)
In the use of non-linear structural performance models, including models that consider the critical over-performance at the failure stage, is very important when performing seismic calculations of reinforced concrete buildings and structures.The use of such models is especially important if the structures have primary damage caused by fire or corrosion, as well as mechanical damage caused by force factors. The purpose of this study is to develop an analytical model of the deformation of eccentrically compressed reinforced concrete columns by considering the failure stage, which includes processes such as peeling of the protective layer, reduction of the stability of the compressed reinforcement and softening of the encased concrete after reaching the design strength. , the existing models that describe the residual behavior of reinforced concrete structures under low cycle loading have been investigated. The models are analyzed considering monotonic curves, which are cyclic deformation boundaries. The model proposed in the research is constructed by analyzing the stages of the stress-strain state of a reinforced concrete column. At each stage, formulas are found for determining moment and curvature by solving equations of equilibrium of internal forces. Calculations based on the obtained model for a particular reinforced concrete column are carried out, monotonous diagrams are obtained, and a conclusion about the significant influence of the level of axial load on the character of deformation is made. On the basis of the obtained model, the construction of hysteresis diagrams under low-cycle loading is expected in the future.